Analysis of imagery in Helena Natasha’s “Love, Spelled in Poetry” poetry collection - Fahira Mauliga; Eusabinus Bunau; Wardah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research analyzes twenty-five selected poems from Helena Natasha's poetry collection 'Love, Spelled in Poetry' to identify imagery types and explore their contribution to meaning and emotional impact. The study addresses the challenge many students face in comprehending imagery and deeper meanings in poetry, often due to lack of critical engagement during reading. A qualitative descriptive method was employed, examining twenty-five poems from the eighty-five-poem collection through close reading and systematic documentation. The findings reveal that Helena Natasha employs various types of imagery, including visual, auditory, tactile, olfactory, gustatory, organic, and kinesthetic, with visual imagery being the most dominant. Visual imagery dominates, followed by organic and kinesthetic imagery. This research contributes to understanding contemporary poetry's use of imagery and highlights its educational value for English as a Foreign Language (EFL) learners in developing language skills, critical thinking, and literary appreciation.